Implementation And Innovation Of Population Administration Services In Central Bengkulu Regency (Study In Durian Demang Village, Karang Tinggi District) - Devy Marjoyo; Witi Rusma Yunita; Kopli Ansori (IJOSMAS, 2026)
Population administration services are a fundamental form of public service in people's lives, as they directly relate to legal identity and access to various social services. This study aims to analyze the implementation of population administration services and public service innovations in Durian Demang Village, Karang Tinggi District, Central Bengkulu Regency. The research method used was a descriptive qualitative approach, with data collection techniques through interviews, observation, and documentation. The results indicate that the implementation of population administration services in Durian Demang Village has been quite successful based on indicators of communication, resources, implementer attitudes, and bureaucratic structure. However, several obstacles remain, such as limited infrastructure, a lack of public understanding of service procedures, and the suboptimal use of information technology. Furthermore, digital-based service innovations in the Bengkulu region, such as the SLAWE application and the Three in One program, show significant potential for improving the quality of public services, although they still face challenges in terms of socialization and human resource capacity. The study's conclusion confirms that improving the quality of public services in Bengkulu requires strengthening the capacity of civil servants, technology-based innovation, and increased public participation.